2013
DOI: 10.4028/www.scientific.net/ssp.205-206.224
|View full text |Cite
|
Sign up to set email alerts
|

PL and DLTS Analysis of Carbon-Related Centers in Irradiated P-Type Cz-Si

Abstract: Photoluminescence (PL) and deep level transient spectroscopy (DLTS) have been used to investigate carbon related defects in p–type Cz–Si induced by proton irradiation. The interstitial carbon–interstitial oxygen (CiOi) level in DLTS and the corresponding C–line (789.5 meV) in PL spectra are detected in as–irradiated samples. Formations of the so–called P–line at 767 meV in PL and a new defect level at about 0.39 eV above the valence band edge, Ev, in the DLTS spectra are observed in the annealed samples. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Then, after annealing at 400 °C for 6.5 h, C i O i is reduced in a correlation with growth of C i O 2i , and after annealing at 400 °C for 23.5 h, C i O i is completely annealed out. We should mention here that in a previous study of C i O i thermal evolution by Raeissi et al, a reduction of most of the C i O i peak takes place after 1 h annealing at 400 °C, while it required several hours at 400 °C in the present study. This could be attributed to the importance of the revers reaction C i O i ↔ C i + O i , which can be significant since O i is the dominant impurity in the material.…”
Section: Resultssupporting
confidence: 42%
See 1 more Smart Citation
“…Then, after annealing at 400 °C for 6.5 h, C i O i is reduced in a correlation with growth of C i O 2i , and after annealing at 400 °C for 23.5 h, C i O i is completely annealed out. We should mention here that in a previous study of C i O i thermal evolution by Raeissi et al, a reduction of most of the C i O i peak takes place after 1 h annealing at 400 °C, while it required several hours at 400 °C in the present study. This could be attributed to the importance of the revers reaction C i O i ↔ C i + O i , which can be significant since O i is the dominant impurity in the material.…”
Section: Resultssupporting
confidence: 42%
“…Several luminescence studies have argued that the P‐line is associated with carbon‐ and oxygen‐related defects, and most likely to an oxygen dimer bonded to C i . Later, a correlation has been found between P‐line and a DLTS peak at E V +0.39 eV that forms upon annealing of C i O i . This peak has been tentatively identified as an interstitial carbon–interstitial dioxygen complex (C i O 2i ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent deep level transient spectroscopy (DLTS) studies have monitored the decay of the C i O i pair and the formation of the C i O 2i structure via the observation of the corresponding electronic levels at E V + 0.36 eV and E V + 0.39 eV [17] . These conclusions are in agreement with previous PL and DLTS measurements referring to the investigation of the C i O 2i defect [18,19]. It was suggested that the annealing of the C i O i occurs via dissociation into C i and O i , where a percentage of the released C i atoms are trapped by oxygen dimers to form the C i O 2i [17,18].…”
Section: Introductionsupporting
confidence: 92%
“…An important point: In our studies of electron irradiated silicon, the 1020 cm −1 band is formed around 300 • C upon the decay of the 862 cm −1 band of the C i O i pair. However, in proton-irradiated thermally treated Si, the formation of the C i O 2i occurs at temperatures above 400 • C according to the reaction C i +O 2i → C i O 2i [17][18][19]. The suggested mechanism in the latter reports involves the dissociation of the C i O i and the capture of the liberated carbon interstitials by oxygen dimers.…”
Section: Discussionmentioning
confidence: 99%
“…By implantation of protons which are used in IGBTs and diodes to form field‐stop layers [2], carbon can be transferred to interstitial lattice sites (C I ) where it is highly mobile and can react with O I to form C I O I complexes. These complexes, which are stable up to temperatures of 300–350°C [9], act as recombination centres at a position of 0.36 eV above the valence band [10, 11] and may impact the electrical device performance. In addition, hydrogen that is introduced by proton implantation to form the field‐stop layer can interact with these complexes.…”
Section: Carbon‐ and Oxygen‐related Complexesmentioning
confidence: 99%